Evaluation of Lingual Foramen in the South Indian Population Using Cone-Beam Computed Tomography: A Prospective Cross-Sectional Study - Aswath Nalini (Wolters Kluwer Medknow Publications, 2024)
BackgroundSurgical procedures in the anterior mandibular region require a profound understanding of the complex anatomical structures to ensure patient safety. The lingual foramen (LF) and its intra-osseous canal are pivotal structures, supplying vascular and neural support to the mental region. The prevalence of LF is widely recognized, with variations among populations. MethodsThe study involved 650 adult participants. Data were collected using high-resolution cone-beam computed tomography (CBCT), and statistical analysis was conducted, establishing inter-rater agreement. ResultsThe population had a varied age distribution, with males comprising 53.23% and females comprising 46.77%. The median lingual canal was found in the Supra and Infra spinosum (65.38%). Most participants had lateral lingual canals (60.92%). The most prevalent lingual foramina was 4 (30.62%). The study found no significant associations between gender and LF diameter, distribution in different travel directions, or LF locations. However, males had a slightly larger diameter. ConclusionThe findings provide valuable insights into LF variations based on anatomical locations, and there were no statistically significant differences in measurements across different age groups. This knowledge contributes to the evolving field of oral and maxillofacial surgery, ensuring better patient outcomes.